Schizophrenia Hypothesis: Autonomic Nervous System Dysregulation of Fetal and Adult Immune Tolerance - Carnac, Tamara (Frontiers in Systems Neuroscience, 2022)
The autonomic nervous system can control immune cell activation via both sympathetic adrenergic and parasympathetic cholinergic nerve release of norepinephrine and acetylcholine. The hypothesis put forward in this paper suggests that autonomic nervous system dysfunction leads to dysregulation of immune tolerance mechanisms in brain-resident and peripheral immune cells leading to excessive production of pro-inflammatory cytokines such as Tumor Necrosis Factor alpha (TNF-α). Inactivation of Glycogen Synthase Kinase-3β (GSK3β) is a process that takes place in macrophages and microglia when a toll-like receptor 4 (TLR4) ligand binds to the TLR4 receptor. When Damage-Associated Molecular Patterns (DAMPS) and Pathogen-Associated Molecular Patterns (PAMPS) bind to TLR4s, the phosphatidylinositol-3-kinase (PI3K)-protein kinase B (Akt) pathway should be activated, leading to inactivation of GSK3β. This switches the macrophage from producing pro-inflammatory cytokines to anti-inflammatory cytokines. Acetylcholine activation of the α7 subunit of the nicotinic acetylcholine receptor (α7 nAChR) on the cell surface of immune cells leads to PI3K/Akt pathway activation and can control immune cell polarization. Dysregulation of this pathway due to dysfunction of the prenatal autonomic nervous system could lead to impaired fetal immune tolerance mechanisms and a greater vulnerability to Maternal Immune Activation (MIA) resulting in neurodevelopmental abnormalities. It could also lead to the adult schizophrenia patient’s immune system being more vulnerable to chronic stress-induced DAMP release. If a schizophrenia patient experiences chronic stress, an increased production of pro-inflammatory cytokines such as TNF-α could cause significant damage. TNF-α could increase the permeability of the intestinal and blood brain barrier, resulting in lipopolysaccharide (LPS) and TNF-α translocation to the brain and consequent increases in glutamate release. MIA has been found to reduce Glutamic Acid Decarboxylase mRNA expression, resulting in reduced Gamma-aminobutyric acid (GABA) synthesis, which combined with an increase of glutamate release could result in an imbalance of glutamate and GABA neurotransmitters. Schizophrenia could be a “two-hit” illness comprised of a genetic “hit” of autonomic nervous system dysfunction and an environmental hit of MIA. This combination of factors could lead to neurotransmitter imbalance and the development of psychotic symptoms.